Demonstrating Power - Wouters, Ruud; Walgrave, Stefaan (American Sociological Review, 2017)
How do public opinion signals affect political representatives’ opinion formation? To date, we have only limited knowledge about this essential representative process. In this article, we theorize and examine the signaling strength of one type of societal signal: protest. We do so by means of an innovative experiment conducted among Belgian national and regional politicians. Elected officials were exposed to manipulated television news items covering a protest demonstration. Following Tilly’s previously untested WUNC claim, four features of the event were manipulated: the demonstrators’ worthiness, unity, numerical strength, and commitment. We argue that these protest features present elected officials with useful cues about what (a segment of) the public wants. We find that these cues affect elected officials’ beliefs. The salience they attach to the protest issue, the position they take, and their intended actions all change as a consequence of exposure. The size of a protest event (numbers) and whether the protesters agree among themselves (unity) are the most persuasive protest factors. The effects of the protest signals come on top of strong receiver effects. We find no evidence that elected officials’ predispositions moderate the effects of the protest features.